Uji Toksisitas Ekstrak Metanolik Kombinasi Daun Benalu Teh Dan Daun Benalu Mangga Terhadap Profil Lipid Tikus Betina (Rattus norvegicus) pada Paparan Sub-Kronik 28 Hari - Lestari, Tengku Anggun; Athiroh, Nour; Mubarakati, Nurul Jadid (FMIPA UNISMA, 2020)
Tea Benalu (Scurrula atropurpurea [Bl.] Dans.) and Mango Benalu (Dendrophthoe pentandra L. miq.) containssecondary metabolites with potential antioxidant potential. Antioxidants can inhibit the oxidation process and reduce Total Cholesterol, Triglycerides, Low-Density Lipoprotein (LDL) and increase High-Density Lipoprotein (HDL). The safety of the preparations for the combination of parasites of tea and mango leaves was tested to obtain toxic effects after repeated treatment tests over some time. The purpose of this study was to determine the toxic effects of a combination of methanolic extracts of a combination of tea parasites and mangoes in female rats (Rattus norvegicus) subchronically for 28 days by looking at the results of the clinical biochemical examination on lipid profiles, namely total cholesterol levels, triglycerides, high-density lipoproteins (28%). HDL), and Low-Density Lipoprotein (LDL). The method of this study was experimental with a combination dose of methanol extract of tea parasite leaves and mango parasite leaves at a dose of 250 mg / KgBB, 500 mg / KgBB and 1000 mg / KgBB with 5x replications each treatment. The subjects used white rats (Rattus norvegicus) female Wistar strains aged 6-8 weeks with a minimum body weight of 100 grams. The treatment in this study was in the form of each dose given 5 times a week for 28 days (subchronic toxicity test) orally. Lipid profile levels were analyzed using the one-way ANOVA test. The results showed that the level of control blood lipid profile with a treatment dose of 250 mg / KgBW, 500 mg / KgBW, and 1000 mg / KgBW was not significantly different. The toxicity test of combined extracts of tea leaves and mango parasite leaves of female rat Rattus novergicus on subchronic exposure 28 days with those doses showed no difference tangible between treatments of controls. This means it is safe and does not cause toxic properties in the lipid profile of female wistar rats.Keywords: Lipid Profile, Scurrula atropurpurea, Dendophthoe pentandra, Sub-Chronic Toxicity, Rattus norvegicusÂ ABSTRAKBenalu Teh (Scurrula atropurpurea [Bl.] Dans.) danÂ Benalu Mangga (Dendrophthoe pentandra L. miq.) mengandung metabolit sekunder berpotensi sebagai antioksidan. Antioksidan dapat memperhambat proses oksidasi dan menurunkan Cholesterol Total, Trigliserida, Low Density Lipoprotein (LDL) dan menaikkan High Density Lipoprotein (HDL). Keamanan sediaan kombinasi daun benalu teh dan mangga diuji memperoleh tentang efek toksik setelah uji perlakuan berulang dalam jangka waktu tertentu. Tujuan dari penelitian ini untuk mengetahui efek toksik kombinasi ekstrak metanolik kombinasi daun benalu teh dan mangga pada tikus betina (Rattus norvegicus) secara subkronik selama 28 hari dengan melihat hasil pemeriksaan biokimia klinis pada profil lipid, yaitu kadar Cholesterol Total, Trigliserida, High Density Lipoprotein (HDL), dan Low Density Lipoprotein (LDL). Metode penelitian ini adalah eksperimental dengan perlakuan dosis kombinasi ekstrak metanol daun benalu teh dan daun benalu mangga dosis 250 mg/KgBB, 500 mg/KgBB dan 1000 mg/KgBB dengan ulangan 5x tiap perlakuan. Subjek menggunakan tikus putih (Rattus norvegicus) betina strain wistar yang berumur 6-8 minggu dengan berat badan minimal 100 gram. Perlakuan dalam penelitian ini berupa setiap dosisÂ diberikan 5 kali seminggu selama 28 hari (uji toksisitas subkronik) secara per-oral. Kadar profil lipid dianalisis menggunakan uji One-way ANOVA. Hasil penelitian menunjukkan bahwa kadar profil lipid darah kontrol dengan perlakuan dosis 250 mg/KgBB, 500 mg/KgBB dan 1000 mg/KgBB tidak berbeda nyata. Ujiâ€toksisitasâ€ekstrak kombinasi daun benalu teh dan daun benalu mangga Â tikus betina Rattus novergicus pada paparan subkronik 28 hari denganâ€dosisâ€tersebut menunjukkan hasil tidakâ€bedaâ€nyata antara perlakuan terhadapâ€kontrol. â€Hal ini berarti aman dan tidak menimbulkan sifat toksik pada profil lipid tikus wistar betina.Kata Kunci : Profil Lipid, Scurrula atropurpurea, Dendophthoe pentandra, Subkronik, Rattus norvegicus